Make : rockets : down-to-Earth rocket science - Westerfield, Mike (Make (Sebastopol, Calif.), 2014)
Starting with the basics of rocket propulsion, readers will start out making rockets made from stuff lying around the house, and then move on up to air-, water-, and solid propellant-powered rockets.